Fear of Missing Out (FOMO), Loneliness, and Social Media Addiction in Early Adults - Fatimah Inanda Putri Luth; Effy Wardati Maryam (Faculty of Psychology, Universitas Semarang, 2024)
Early adulthood is a critical period in the development of collaborative communication skills, and management of various aspects of life, where excessive use of social media can lead to addiction with negative impacts on physical health, psychological, and interpersonal relationships. This study aims to understand the relationship between Fear of Missing Out (FOMO) and loneliness with the level of social media addiction in the early adult population. The type of research used is quantitative correlational. The population of this study is Sidoarjo district residents aged 20-40 years, totaling of samples was 348. The research sample collection technique used Convenience Sampling. The research data analysis technique was analyzed using multiple linear regression techniques. The results showed a p value of 0.001